Reducing Criminality and Saving Energy - Martins de Moracs, Thiago Matheus [UNESP]; Santos Petri, Lucas de Paula [UNESP]; IEEE (Ieee, 2016)
One of the biggest problems faced by the Brazilian population is high crime rates and current public policies are ineffective to ensure public safety. Given the reduction in crimes committed at bus stops and maximum energetic efficiency since Brazil is going through the greatest energy crisis of the last 15 years, it was created and designed a way to, simultaneously, reduce crime rates and save energy by creating a sustainable lighting system at bus stops that depends exclusively on solar energy. That system can be easily deployed at any public place with simple engineering concepts and with no costs to keep it running.
Keywords: Criminality; Light; Efficiency; Solar